Content and composition of lipid classes, fatty acid from \(Sargassum\) seaweed collected at Con Dao and Van Phong bay - Pham, Thu Hue; Nguyen, Van Tuyen Anh Nguyen; Thi Hoang, Yen Kieu; Nguyen, Nguyen; Hoang, Hai Nam; Pham, Quoc Long; Dam, Duc Tien; Tran, Thi Thanh Van; Le, Tat Thanh (Vietnam Journal of Marine Science and Technology, 2021)
This study studied the content and composition of the total lipid, lipid classes and fatty acids in 13 brown seaweed Sargassum species collected from Con Dao and Van Phong, Vietnam. The total lipid has a low content and varies among species from 0.10–1.70% of the fresh weight. From 13 species, seven lipid classes including polar lipid (Pol), free fatty acids (FFA), sterol (ST), hydrocarbon and wax (HW), triacylglycerol (TG), diacylglycerol (DG), and monoalkydiacylglycerol (MADG). Using the GC-FID technique, we have identified 29 fatty acids classified into 3 groups of saturated fatty acid, monounsaturated fatty acids, polyunsaturated fatty acids with an average content of 44.93%, 24.57% and 27.44%, respectively. Among those, many value fatty acids have been detected with high content such as C18:3n-3, C20:4n-6, 20:5n-3, and 22:6n-3. The lipid of 13 brown seaweed Sargassum species also fully contains omega-3,6,9 fatty acids with the content of 9.28%, 16.28% and 16.63%, respectively.